A REVIEW ON KNOWLEDGE MANAGEMENT DISCIPLINE - Jafari, Mostafa; Akhavan, Peyman; Mortezaei, Ashraf (Journal of Knowledge Management Practice, 2009)
This paper aims to provide the organizational roles to implement knowledge management. The focus is on how to devise and implement knowledge management where it is required and provides a common understanding about KM in implementation area. This paper also provides a general review on KM systems, KM architecture, KM process, KM strategy and KM critical success factors.
Keywords: Knowledge management; Knowledge strategy; Knowledge architecture